Pancasila dan Deradikalisasi Berbasis Agama - Ridwan, Nur Khalik (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2013)
Pancasila is the state foundation and national philosophy that is received by the majority of the Indonesian people. Religious education with no concept of Pancasila makes only the generation of separation instead of national integration that is needed by the nation of Indonesia. Religious education must be the education of sensitive peace, sensitive to people’s issues and social justice that is as an important part of the Pancasila and the needs of our nation. Religious education becomes an important part to increase faith, to have a good nation, and to make a good beliver and patriotic.